2018
DOI: 10.1002/hed.25568
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of calcium excretion and calcium/creatinine clearance ratio in the differential diagnosis of familial hypocalciuric hypercalcemia and primary hyperparathyroidism

Abstract: Background Twenty‐four‐hour renal calcium‐excretion (CE) and calcium/creatinine‐clearance‐ratio (CCCR), respectively, are widely used to rule out familial hypocalciuric hypercalcemia (FHH) in patients with suspected primary hyperparathyroidism before surgery. The aim was to evaluate the practicability of CE compared to CCCR. Patients and Methods We analyzed biochemical parameters, surgical treatment, gene mutation results, and long‐term follow‐up data of 198 patients (including 14 patients with FHH) and the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
0
12
0
2
Order By: Relevance
“…On the other hand, the pathogenic variant detection rate for FHH (types 1 and 3) was 32% in those with a CCCR ≤ 0.01 and 19% in those with CCCR < 0.02. Similarly, others have also found that CCCR was not reliable in distinguishing between PHPTH and FHH and in one large cohort, nearly two thirds of patients with a CCCR < 0.02 had surgically confirmed PHPTH 18,19 …”
Section: Discussionmentioning
confidence: 87%
“…On the other hand, the pathogenic variant detection rate for FHH (types 1 and 3) was 32% in those with a CCCR ≤ 0.01 and 19% in those with CCCR < 0.02. Similarly, others have also found that CCCR was not reliable in distinguishing between PHPTH and FHH and in one large cohort, nearly two thirds of patients with a CCCR < 0.02 had surgically confirmed PHPTH 18,19 …”
Section: Discussionmentioning
confidence: 87%
“…Each student solved 4 Bayesian cases, which consisted of different medical contexts from the field of clinical endocrinology: Cushing’s syndrome, 38 familial hypocalciuric hypercalcemia (FHH), 39 primary aldosteronism, 40 and thyroid cancer. 1…”
Section: Methodsmentioning
confidence: 99%
“…Material and medical context. Each student solved 4 Bayesian cases, which consisted of different medical contexts from the field of clinical endocrinology: Cushing's syndrome, 38 familial hypocalciuric hypercalcemia (FHH), 39 primary aldosteronism, 40 and thyroid cancer. 1 Endocrinology was selected because in this field of internal medicine, there is a great discrepancy between very frequent diseases in the population.…”
Section: Methodsmentioning
confidence: 99%
“…Vor chirurgischen Eingriffen an den Nebenschilddrüsen sollte eine FHH deshalb ausgeschlossen werden, um unnötige Operationen zu vermeiden [10,11].…”
Section: äTiologieunclassified